The unbearable weight of aging: How to deal with the "demographic time bomb" - Yeva Nersisyan; Xinhua Liu; L. Randall Wray (Levy Economics Institute of Bard College, 2023)
The aging of the global population is in the headlines following a report that China's population fell as deaths surpassed births. Pundits worry that a declining Chinese workforce means trouble for other economies that have come to rely on China's exports. France is pushing through an increase of the retirement age in the face of what is called a demographic "time bomb" facing rich nations, created by rising longevity and low birthrates. As we approach the debt limit in the US, while President Biden has promised to protect Social Security, many have returned to the argument that the program is financially unsustainable. This paper argues that most of the discussion and policy solutions proposed surrounding aging of populations are misfocused on supposed financial challenges when they should be directed toward the challenges facing resource provision. From the resource perspective, the burden of caring for tomorrow's seniors seems far less challenging. Indeed, falling fertility rates and an end to global population growth should be welcomed. With fewer children and longer lives, investment in the workers of the future will ensure growth of productivity that will provide the resources necessary to support a higher ratio of retirees to those of working age. Global population growth will peak and turn negative, reducing demands on earth's biosphere and making it easier to transition to environmental sustainability. Rather than facing a demographic "time bomb," we can welcome the transition to a mature-aged profile.
Keywords: H51; H55; H61; J11; J13; J14; J26; 330; Aging; population bomb; demographic time bomb; dependency ratios; birthrates; longevity